Wired Enzymes in mesoporous materials: A benchmark for fabricating biofuel cells - Catalano, Paolo Nicolás; Wolosiuk, Alejandro; Soler Illia, Galo Juan de Avila Arturo; Bellino, Martin Gonzalo (Elsevier Science Sa, 2015)
Fil: Catalano, Paolo Nicolás. Comisión Nacional de Energía Atómica; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina